Rosmarinic Acid Methyl Ester Regulates Ovarian Cancer Cell Migration and Reverses Cisplatin Resistance by Inhibiting the Expression of Forkhead Box M1 - Soo Hyun Lim; Ki Hong Nam; Kyungtae Kim; Sang Ah Yi; Jaecheol Lee; Jeung-Whan Han (MDPI AG, 2020)
Rosmarinic acid methyl ester (RAME), a derivative of rosmarinic acid (RA), is reported to have several therapeutic effects, including anti-tumor effects against cervical cancer. However, its anti-tumor effects in ovarian cancer is unclear. In this study, we studied the molecular pathways associated with the anti-tumor effects of RAME in ovarian cancer. To identify the effects of RAME in ovarian cancer, RNA sequencing was performed in RAME-treated ovarian cancer cells; we found that RAME treatment downregulated the genes closely involved with the target genes of the transcription factor Forkhead box M1 (FOXM1). It was reported that FOXM1 is overexpressed in a variety of cancer cells and is associated with cell proliferation and tumorigenesis. Therefore, we hypothesized that FOXM1 is a key target of RAME; this could result in its anti-tumor effects. Treatment of ovarian cancer cells with RAME-inhibited cell migration and invasion, as shown by wound healing and transwell migration assays. To examine whether RAME represses the action of FOXM1, we performed quantitative RT-PCR and ChIP-qPCR. Treatment of ovarian cancer cells with RAME decreased the mRNA expression of FOXM1 target genes and the binding of FOXM1 to its target genes. Moreover, FOXM1 expression was increased in cisplatin-resistant ovarian cancer cells, and combination treatment with RAME and cisplatin sensitized the cisplatin-resistant ovarian cancer cells, which was likely due to FOXM1 inhibition. Our research suggests that RAME is a promising option in treating ovarian cancer patients, as it revealed a novel molecular pathway underlying its anti-tumor effects.